Performance Comparison and Structure Adjustment of Insurance Business of Property Insurance Companies - Le, Min (Archives of Business Research, 2019)
The insurance business structure directly affects the profitability and sustainable development of property insurance companies. It is more meaningful to study how to adjust the business structure to achieve better performance in the context of diversified insurance operation than to argue about the diversified operation and specialized operation. The research compares the performance of insurance business lines based on rich data of three dimensions: insurance business lines, companies and time. The results indicate that motor insurance has a medium and low level of performance, while household property insurance has a high profitability and the performance is in good equilibrium and stability. Then this paper introduces a cost-volume-profit（C-V-P）model under uncertainty as quantitative decision-making tools for the adjustment of the business structure of property insurance companies. Uncertainty comes from the variable costs of property insurance companies.